Oral hygiene and its correlation with the general health of dependent elderly people: A literature review (Research, Society and Development, 2021)
The present study aimed to search the literature for works related to oral hygiene practices and the possible impacts on the general health conditions of the dependent elderly. This is an integrative bibliographic review. The research was carried out in the electronic databases PubMed (MEDLINE), BBO, LILACS and SCIELO, in the month of April 2021, using the descriptors “Oral Hygiene”; "Frail Elderly"; “Health of the Elderly”; “Dental Care for Aged”. Scientific articles in Portuguese and English, published in the last five years (2016 to 2021) were included. 129 articles were found, of which 26 were excluded due to duplication. Thus, the titles and abstracts of 103 articles were analyzed, selecting 43 to be read in full. Of these, 15 were selected and included in this study because they meet the pre-established inclusion criteria. Among the selected studies, there is a predominance of studies carried out in Brazil (11), cross-sectional studies (12) and the approach to factors related to dental prosthesis (4) and quality of life (3). In view of the results discussed, it is evident that there is a gap regarding dental care for institutionalized or non-institutionalized elderly, which is aggravated by socioeconomic conditions. In addition, there is a need for public policies for comprehensive care for the dependent elderly population.